The Polish Cryptanalysis of Enigma (Research Journal of Mathematics & Technology, 2022)
The cryptanalysis of the Enigma cipher machine during World War II by British and Americancodebreakers led by Alan Turing at Bletchley Park has been well-documented, and rightfully recognized as one of the supreme achievements of the human intellect. However, without the successful cryptanalysis of an earlier version of Enigma by Polish codebreakers led by Marian Rejewskiin the 1930s, the work of the British and Americans in the 1940s might have taken much longer,prolonging the war at the potential cost of untold additional lives. The mathematics integral tothe Polish cryptanalysis of Enigma involved some basic theory of permutations. The purpose ofthis paper is to present an overview of these ideas and how they served to this effect. To assist indemonstrating this, technology involving Maplets will be used.